Museum and public school partnerships: A step-by-step guide for creating standards-based curriculum materials in high school social studies - Barragree, Cari (Kansas State University, 2007)
The purpose of the study was to research, develop, and validate a step-by-step guide for museum and public school partnerships that wish to create motivational standards-based curriculum materials in high school social studies. Museum and Public School Partnerships: A Step-by-Step Guide for Creating Motivational Standards-Based Curriculum Materials in High School Social Studies was developed using the research and development methodology of Borg and Gall (1989). The research and development process used in this study included seven steps: 1) research analysis and proof of concept, 2) product planning and design, 3) preliminary product development, 4) preliminary field testing, 5) revision of the prototype, 6) main field testing, and 7) revision of the final product. A prototype of the guide was produced and then evaluated by museum and public school experts in the preliminary field test. Revisions were made to the guide based on their feedback. The guide was then distributed to practitioners in the main field test. The reviewers in the main field test were museum staff or high school history educators; or museum, curriculum, or technology directors in the United States. Feedback from the main field test was used to create the final product. Major conclusions of the study were: a) there was a lack of literature specifically for museum and public school partnerships that wished to create motivational standards-based curriculum materials for high school social studies, b) museum and public school personnel benefit from quality resource step-by-step guides, c) educational guides developed through research and development methodology offer museum and public school personnel practical and valuable products for improving education, d) a step-by-step guide is a useful tool when museums and public schools partner to create motivational standards-based curriculum materials for high school social studies, e) this study produced the first step-by-step guide for museums and public schools that wish to partner to create motivational standards-based curriculum materials for high school social studies.
Keywords: Museum and public school partnerships; Social studies; Standards-based curriculum; Student motivation; High school; partnership; Education, Curriculum and Instruction (0727); Education, Secondary (0533); Education, Social Sciences (0534)